Phytochemical Screening, Antimicrobial and Antifungal Activities of Zingiber officinale Collected from Dang and Arghakhanchi Districts of Nepal - Banjade, Purnima; Chand, Anand Bahadur; Pokhrel, Galaxy; Mahato, Ajaya; Silwal, Sachin; Bagle, Shiva; Khanal, Ranjana; Ghimire, Pratima; Pokhrel, Ganga Raj (BMC Journal of Scientific Research, 2025)
Phytochemical screening, Antimicrobial and antifungal activities of rhizomes extracts of Zingiber officinale, grown in Dang and Arghakhanchi districts of Nepal, in different solvents is still not under stood clearly. The rhizomes of the plant were collected, dried, chopped, powdered and subjected for extraction using maceration technique. The solvent methanol (MeOH), dichloromethane (DCM) and ethyl acetate (EtOAc) were used for the extraction of secondary metabolites. Phytochemical screening, antimicrobial activity and antifungal activities were gauged in the extract of different solvents. Efficient antimicrobial activity, especially against S. aureus and P. aeruginosa, was observed in ethyl acetate (EtOAc) extract of sample collected from Dang district (S2 ). Strong antifungal activities were exhibited in methanolic extract sample of both Arghakanchi (S1) and Dang districts (S2 ). Extracts of all ginger samples do not show any zone of inhibition against E. Coli. Rhizome extracts of both samples (S1 and S2 ) show potentiality against microbial and fungal infections.